Spatiotemporal monitoring of the rare northern dragonhead (Dracocephalum ruyschiana, Lamiaceae) — SNP genotyping and environmental niche modeling herbarium specimens. Issue 8 (12th August 2022) - Nygaard, Malene; Kopatz, Alexander; Speed, James M. D.; Martin, Michael D.; Prestø, Tommy; Kleven, Oddmund; Bendiksby, Mika
Abstract: The species we have studied the spatiotemporal genetic change in the northern dragonhead, a plant species that has experienced a drastic population decline and habitat loss in Europe. We have added a temporal perspective to the monitoring of northern dragonhead in Norway by genotyping herbarium specimens up to 200 years old. We have also assessed whether northern dragonhead has achieved its potential distribution in Norway. To obtain the genotype data from 130 herbarium specimens collected from 1820 to 2008, mainly from Norway (83) but also beyond (47), we applied a microfluidic array consisting of 96 SNP markers. To assess temporal genetic change, we compared our new genotype data with existing data from modern samples. We used sample metadata and observational records to model the species' environmental niche and potential distribution in Norway. Our results show that the SNP array successfully genotyped all included herbarium specimens. Hence, with the appropriate design procedures, the SNP array technology appears highly promising for genotyping old herbarium specimens. The captured genetic diversity correlates negatively with distance from Norway. The historical‐modern comparisons reveal similar genetic structure and diversity across space and limited genetic change through time in Norway, providing no signs of any regional bottleneck (i.e., spatiotemporal stasis). The regional areas in Norway have remained genetically divergent, however, both from each other and more so from populations outside of Norway, rendering continued protection of the species in Norway relevant. The ENM results suggest that northern dragonhead has not fully achieved its potential distribution in Norway and corroborate that the species is anchored in warmer and drier habitats. Abstract : Our study provides new insight to guide conservation priorities for the charismatic flowering plant called northern dragonhead ( Dracocephalum ruyschiana ). It also showcases a fruitful integration of methods and data sources that jointly enables a holistic species assessment covering space and time.